2018
DOI: 10.1002/mabi.201800147
|View full text |Cite
|
Sign up to set email alerts
|

Combining Catalyst‐Free Click Chemistry with Coaxial Electrospinning to Obtain Long‐Term, Water‐Stable, Bioactive Elastin‐Like Fibers for Tissue Engineering Applications

Abstract: Elastic fibers are a fundamental requirement for tissue-engineered equivalents of physiologically elastic native tissues. Here, a simple one-step electrospinning approach is developed, combining i) catalyst-free click chemistry, ii) coaxial electrospinning, and iii) recombinant elastin-like polymers as a relevant class of biomaterials. Water-stable elastin-like fibers are obtained without the use of cross-linking agents, catalysts, or harmful organic solvents. The fibers can be directly exposed to an aqueous e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Indeed, it can be found that the ELRs chemical modifications could be carried out through the functionalization of amino groups of the lysines, for example, with azido and cyclooctyne groups [ 20 , [34] , [35] , [36] ]. Thus, the ELRs chains (e.g., VKV24) can be chemically cross-linked by means of catalyst-free click chemistry (azide−alkyne [3 + 2] cycloaddition) [ 20 , 34 , 52 , 53 ]. This resulted in a hydrogels structure with a G′ of about 1.8 kPa–7.5 kPa as the concentration increases from 50 to about 150 mg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it can be found that the ELRs chemical modifications could be carried out through the functionalization of amino groups of the lysines, for example, with azido and cyclooctyne groups [ 20 , [34] , [35] , [36] ]. Thus, the ELRs chains (e.g., VKV24) can be chemically cross-linked by means of catalyst-free click chemistry (azide−alkyne [3 + 2] cycloaddition) [ 20 , 34 , 52 , 53 ]. This resulted in a hydrogels structure with a G′ of about 1.8 kPa–7.5 kPa as the concentration increases from 50 to about 150 mg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group obtained oriented electrospun clickable ELR fibers, which have proven good cytocompatibility with fibroblasts and keratinocytes in vitro, suggesting their potential application in the formation of artificial skin or to promote skin regeneration [111]. Contemporarily, Fernández-Colino et al achieved similar fibers, which highlights their ease of attainment and their potential application in different tissue engineering fields [112].…”
Section: Elrs For Enhancing Implant Vascularizationmentioning
confidence: 94%
“…[256] Electrospun ELR-based nanofiber matrices have been used to develop 3D scaffolds for several applications, which include dermal repair and as vascular grafts studies. [257][258][259] Similarly, salt leaching coupled with gas foaming has been used to produce macroporous scaffolds based on crosslinked ELR hydrogels. [260,261] This technique enables the pore size to be tuned on the microscale for optimal cell interaction as per requirement.…”
Section: Architecture and Stiffness Controlmentioning
confidence: 99%